Soluções propostas para a infraestrutura de redes do laboratório de informática educacional da escola estadual Prof.ª Maria Cavalcante de Azevedo Picanço - CUNHA, Marcelo Souza (Instituto Federal do Amapá, 2021)
Over the years, information technology continues to evolve, making it easier to perform certain tasks. With that, the need arose to try to follow this evolution. The present work had as main objective to analyze the real situation of the wired network infrastructure of the LIED (Educational Informatics Laboratory) of EEMCAP (State School Maria Cavalcante de Azevedo Picanço). In this context, a case study was carried out based on structured cabling standards to identify the quantity, status of equipment that is part of the local computer network and to identify possible irregularities in the installation and maintenance of the structure. As a result of the study, it was evident the lack of some essential equipment for the functioning of the structure and installations made in disagreement with the current rules. Therefore, it was proposed to change the location of some equipment and replace damaged parts to improve the performance of the network.